Rising Incidence of Pediatric Otitis Media and The Role of Antibiotic Resistance - Shah, Sayyed Muddasir; Zaman, Haider; Ullah Jan, Mubashar; Khan, Noor Hayat; Ali, Majid; Malik, Usman Afzal (Journal of Neonatal Surgery, 2025)
Background: Even adding this type of ear infection to the list of common childhood illnesses produces a lot of antibiotic prescriptions. Because of environmental risks and poor use of antibiotics, more cases of antibiotic resistance are appearing all over the globe. As a result, there are more cases of drug-resistant bacteria and patients experience more recurrences, more complications and more hassles with medical care. Objectives: To evaluate current trends in pediatric otitis media, assess patterns of antibiotic resistance among causative organisms, and analyze associated outcomes and the risk factors for recurrent infections. Study Design: a cross-sectional study Place and duration of study. Department Of ENT Mardan Medical Complex,Bacha Khan Medical College Mardan, KPK During The Period From January To December 2023 Methods: 300 children ranging from 6 months to 12 years old who all had otitis media confirmed by a doctor. A culture of the middle ear fluids was done and the findings were tested against various bacteria. We recorded information about the person’s age, medicine history and any previous infections. All statistical analysis was carried out with SPSS v24.0 and the significance level was p<0.05. Results: 300 children the average age was 3.8 years with a standard deviation of 2.4 years. For every man there were 1.3 women in the country. Streptococcus pneumoniae (42%) and Haemophilus influenzae (35%) accounted for most of the findings. Among the cases, resistance to amoxicillin-clavulanate was recorded in 53% of them, whereas 28% of patients showed resistance to macrolides. Having taken antibiotics within the past 30 days made it much more likely to develop a resistant strain (p=0.02). Thirty-one percent of patients experienced a relapse, mostly those with multidrug-resistant forms of infection. Conclusion: An increase in pediatric otitis media is connected to a rising problem with antibiotic resistance. Because amoxicillin-clavulanate is highly resisted, using antibiotics wisely and treating with culture recommendations is very important. Expanding vaccination, helping caregivers and regular monitoring of microbes helps prevent the same disease from coming back and complications related to resistance.